Identification of social innovation in health criteria in Latin America - Diana Castro-Arroyave; Luisa Fernanda Duque-Paz (BMJ Open)
Objectives Understanding the Latin American Social Innovation in Health (SIH) approach requires a process of typifying and identifying main criteria of the approach based on the employed practices of different health initiatives implemented throughout the region. This article presents a descriptive analysis of the main criteria of SIH.Design To identify the theoretical and methodological developments of SIH between the years 2013 and 2018, a scoping review was conducted using a mixed approach. 80 texts in English, Spanish and Portuguese were screened through a reflexive analysis process involving intratextual and intertextual reading.Setting and participants The documentary research covered journals, books and higher degree theses addressing experiences or theoretical constructs developed in the Latin American region.Primary and secondary outcome measures The approaches identified in the studied initiatives were mutually complementary; moreover, based on the typification of the main criteria between approaches and implementation proposals, the convergences and divergences between SIH and other approaches found in the sample were identified. In most cases, the different approaches in the sample are committed to initiatives that include some degree of innovation, improve access to healthcare services and recognise in one way or another a public policy in line with the Sustainable Development Goals (SDGs).Results Eighteen characteristic criteria were identified, of which nine particularly differentiate SIH from other approaches conceptually and methodologically. Further work is essential to eliminate the vague delimitation between social and technological aspects of innovation.Conclusions The findings indicate that although the SIH concept is in construction, it is advancing down a path of recognition in the region, defining its role as an important field of study on social transformation in health and development.